Steric Control of Geminal Lewis Pair Behavior: Frustration Induced Dyotropic Rearrangement - Dorkó, Éva; Varga, Eszter; Gáti, Tamás; Holczbauer, Tamás; Pápai, Imre; Mehdi, Hasan; Soós, Tibor (Synlett, 2014)
A series of methylene-linked boron/nitrogen geminal Lewis pairs were synthesized and the impacts of sterical effect on their chemical behavior were systematically investigated. Increasing the steric demand around the boron atom is manifested first by an incremental change in the structure of the resulting dative adducts. Accordingly, in the case of phenyl substituents (Alk2NCH2BPh2), formation of head-to-tail dimers/oligomers was observed, while such an intermolecular association was avoided when o-tolyl moiety was introduced [Alk2NCH2B(o-Tol)2], affording only an intramolecular dative complex. Further increase of sterical hindrance to a point (i.e. using mesityl substituents), however, caused a radical change in the structure; a dyotropic rearrangement occurred. Thus, steric interference induced a rearrangement in the geminal pair to relieve or minimize the frustration strain.
Keywords: Lewis acids; boron; steric hindrance; dyotropic rearrangement; frustrated Lewis pairs